A taxonomic revision of the genus Tentyria Latreille, 1802 in the Peninsula and Balearic (Coleoptera: Tenebrionidae) - Bujalance, José L.; Ferrer, Julio; Cárdenas, Ana M. (Zootaxa, 2023)
In this work entomological material and nomenclatural types of the Ibero-Balearic species of Tentyria Latreille, 1802 genus are revised. A reordination in groups of species and a new classification of valid species are proposed. Thirteen groups of species including 31 species and six subspecies have been established. Seven new species of Iberian Tentyria are described and figured, including two from Portugal: Tentyria stupefacta sp. nov. and Tentyria faroensis sp. nov.; and five species from Spain: Tentyria espanoli sp. nov., Tentyria kochi sp. nov., Tentyria striatorugosa sp. nov., Tentyria castrotovari sp. nov. and Tentyria pseudogaditana sp. nov. Three new subspecies: Tentyria sinuatocollis ssp. escalerai nov., Tentyria velox ssp. serrana nov., Tentyria sublaevis ssp. cognata nov., are also described. The true identity of 14 species historically confused is argued: Tentyria curculionoides (Herbst, 1799); Tentyria peiroleri Solier, 1835; Tentyria incerta Solier, 1835; Tentyria levis Solier, 1835; Tentyria sinuatocollis Rosenhauer, 1856; Tentyria prolixa Rosenhauer, 1856; Tentyria rugosostriata Kraatz, 1865; Tentyria corrugata Rosenhauer, 1856; Tentyria velox Chevrolat, 1865; Tentyria sublaevis Kraatz, 1865; Tentyria heydeni Haag-Rutenberg, 1870; Tentyria lateritia Reitter, 1900; Tentyria castiliana Koch, 1944; and Tentyria aragonica Koch, 1944. The taxonomic status and the name Tentyria subrugosa Solier, 1835 have been modified because it is a primary homonym of Tentyria subrugosa Besser, 1832. Tentyria elongata Waltl, 1835 is a primary homonym of Tentyria elongata Gebler, 1829 (= Anatolica angustata (Steven, 1828)). The taxonomic status of Tentyria grossa ssp. basalis Schaufuss, 1869 is also re-established. Lectotypes of 14 species are designated; seven synonymies are established (one of them from the Italian fauna). The distribution of species is indicated and, agreeing with the new taxonomical classification, a key of species is also provided.